Hydrochemistry and weathering at Pardo River basin, São Paulo State, Brazil - Bonotto, Daniel Marcos [UNESP] (Springer Nature, 2023)
This work was conducted at the Pardo River hydrographic basin, which is a federal watershed belonging to the Paranapanema River hydrographic basin (PRHB) in Brazil (São Paulo State and Paraná State). The aim was to realize an integrated hydrochemical and radiometric (U-isotopes and 210Po) approach, highlighting the water/soil-rock and surface water/groundwater interactions, with implications to the weathering processes occurring there. The study area has been often considered one of the best preserved/unpolluted river in São Paulo State, contributing to the water supply of several cities distributed along its banks. However, the results reported here suggest possible lead diffuse pollution caused by the use of phosphate fertilizers in agricultural activities taking place in the basin. The analyzed groundwaters and surface waters tend to be neutral to slightly alkaline (pH of 6.8–7.7), possessing low mineral concentration (total dissolved solids up to 500 mg/L). SiO2 is the major dissolved constituent in the waters, while bicarbonate is the dominant anion, and calcium is the preponderant cation. The effects of the weathering of silicates to control the dissolution of constituents in the liquid phase have been identified from some diagrams often utilized in hydrogeochemical studies. Chemical weathering rates have been estimated from hydrochemical data associated to analytical results of the natural uranium isotopes 238U and 234U concerning to samples of rainwater and Pardo River waters. The fluxes in this watershed are permitted to obtain the following rates: 11.43 t/km2 year (sodium), 2.76 t/km2 year (calcium), 3.17 t/km2 year (magnesium), 0.77 t/km2 year (iron), and 8.64 t/km2 year (uranium). This new dataset constitutes valuable information for people engaged on the management of the Pardo River watershed, as well as to researchers interested on comparative studies considering the available data from other basins worldwide.
Keywords: Chemical weathering rates; Groundwaters; Hydrochemistry; Pardo River watershed; Surface waters